39-15y=-31-5y

Simple and best practice solution for 39-15y=-31-5y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 39-15y=-31-5y equation:


Simplifying
39 + -15y = -31 + -5y

Solving
39 + -15y = -31 + -5y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '5y' to each side of the equation.
39 + -15y + 5y = -31 + -5y + 5y

Combine like terms: -15y + 5y = -10y
39 + -10y = -31 + -5y + 5y

Combine like terms: -5y + 5y = 0
39 + -10y = -31 + 0
39 + -10y = -31

Add '-39' to each side of the equation.
39 + -39 + -10y = -31 + -39

Combine like terms: 39 + -39 = 0
0 + -10y = -31 + -39
-10y = -31 + -39

Combine like terms: -31 + -39 = -70
-10y = -70

Divide each side by '-10'.
y = 7

Simplifying
y = 7

See similar equations:

| 21y^14-7y^4=0 | | 2y-4x=-3-2x+y | | 8x-5=63 | | (3.2+1)-(0.6*7)= | | Logx(256)=2 | | 5+2y=(-1) | | -14x+2y=-2 | | -3(2a-3)=3(a-6) | | h+4=2h-19 | | z=3*x-y | | y=0.95x | | 9.2-x=7.3 | | -7x+y=-1 | | 3x-11=x-5 | | -3(2x-3)=3(x-6) | | 4x+3=2(2x+2)-2x | | y=0.75(4)x | | 4=-0.5x^2+46 | | 42=12+3p | | 31(2c+4)=2(c+6)+c | | 7[2e-1]-3=6+6e | | 32=7(n+7)+5(5n+3) | | Y+2=.6(x+4) | | 42=2.333333x | | 6x+34x=7 | | 10p-3=2[12+4p]-7 | | 800=2x+3x+10x | | 9g=3[-4+5g] | | 500=2x+8x | | Y=-.6x-1 | | 3j+10=-30 | | .13x+x=141 |

Equations solver categories